Targeted Treatment against Lipoprotein (a): The Coming Breakthrough in Lipid Lowering Therapy - Bożena Sosnowska; Stanisław Surma; Maciej Banach (MDPI AG, 2022)
Atherosclerotic cardiovascular diseases (ASCVD) are a very important cause of premature death. The most important risk factor for ASCVD is lipid disorders. The incidence of lipid disorders and ASCVD is constantly increasing, which means that new methods of prevention and treatment of these diseases are still being searched for. In the management of patients with lipid disorders, the primary goal of therapy is to lower the serum LDL-C concentration. Despite the available effective lipid-lowering therapies, the risk of ASCVD is still increased in some patients. A high level of serum lipoprotein (a) (Lp(a)) is a risk factor for ASCVD independent of serum LDL-C concentration. About 20% of Europeans have elevated serum Lp(a) levels, requiring treatment to reduce serum Lp(a) concentrations in addition to LDL-C. Currently available lipid lowering drugs do not sufficiently reduce serum Lp(a) levels. Hence, drugs based on RNA technology, such as pelacarsen, olpasiran, SLN360 and LY3819469, are undergoing clinical trials. These drugs are very effective in lowering the serum Lp(a) concentration and have a satisfactory safety profile, which means that in the near future they will fill an important gap in the armamentarium of lipid-lowering drugs.